Estudo dos efeitos do extrato de própolis em um modelo murino de angiogênese inflamatória - Sandra Aparecida Lima de Moura (2009)
Propolis is a chemically complex resinous bee product which has gained worldwide popularity as a means to improve health condition and prevent diseases. The main constituents of an aqueous extract of a sample of green propolis from Southeast Brazil were shown by HPLC/MS/MS to be mono- and di-O-caffeoylquinic acids; phenylpropanoids known as important constituents of alcohol extracts of green propolis, such as artepillin C and drupanin were also detected in low amounts in the aqueous extract. The anti-inflammatory activity of this extract was evaluated by determination of wound healing parameters. Female Swiss mice were implanted subcutaneously with polyesther- polyurethane sponge discs to induce wound healing responses, andadministered orally with water extract of green propolis (500 mg/kg). The effects on various components of inflammatory angiogenesis (cell recruitment, blood vessel formation and extracellular matrix deposition) were evaluated at 4, 7 and 14 days postimplantation,. Blood vessel formation as assessed by hemoglobin content and by morphometric analysis of the implants was reduced by WEP compared to the untreatedgroup. The levels of vascular endothelial growth factor (VEGF) increased progressively in the treated group but decreased after day 10 in the control group. Accumulation of neutrophils and macrophages was determined by measuring myeloperoxidase (MPO) and N-acetylglucosaminidase (NAG) activities, respectively. The fibrovascular stroma and deposition of extracellular matrix were evaluated by histopathologic and morphometric analyses. In the propolis-treated group at days 4 and 7 the inflammatory process in the sponge was reduced in comparison with control. Neutrophil accumulation was unaffected by propolis, but NAG activity was reduced by the treatment at day 14. The levels TGF-â1 intraimplant increased progressively in both groups but was higher (40%) at day 14 in the control implants. The pro-inflammatory levels of TNF-á peaked at day 7 in the control implants, and at day 14 in the propolis-treated group. A progressive increase in cell influx and collagen deposition was observed in control and propolis- treated groups during the whole period. However, these effects were attenuated in the propolis-treated group at days 4 and 7, indicating that key factors of the wound healing process are modulated by propolis constituents. Our results indicate that the anti-inflammatory/ anti- angiogenic effects of propolis are associated with cytokine modulation.